2004
DOI: 10.1021/om049959b
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on the Mechanisms of the Reactions of Gas-Phase OsOn+ (n = 1−4) with Methane

Abstract: The sextet, quartet, and doublet potential energy surfaces (PESs) of the reactions of methane with gas-phase OsO n + (n=1−4) have been explored via density functional calculations to investigate the mechanisms of these reactions. For the reactions of OsO n + (n = 1−2) with methane, the minimum energy reaction paths are found to involve two spin inversions in the entrance and exit channels. Specifically, they are most likely to proceed through the following steps:  4OsO+ + CH4 → 2OOsCH4 + → 2OOs(H)CH3 + → 2OO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 100 publications
4
13
0
Order By: Relevance
“…[25] In fact, these DFT results are fully consistent with the qualitative consideration. [8,21,23,25] On the other hand, in contrast to the cation reaction systems, the reactions between neutral metal oxides and methane have not yet received enough attention, partially because of the experimental challenges faced in detecting neutral species in the gas phase. Theoretically, Broclawik's and Hwang's groups have studied the reaction mechanism of neutral metal oxides, MOs (M ¼ Be, Sc, Ni, Pd, Pt, and Rh) with methane.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…[25] In fact, these DFT results are fully consistent with the qualitative consideration. [8,21,23,25] On the other hand, in contrast to the cation reaction systems, the reactions between neutral metal oxides and methane have not yet received enough attention, partially because of the experimental challenges faced in detecting neutral species in the gas phase. Theoretically, Broclawik's and Hwang's groups have studied the reaction mechanism of neutral metal oxides, MOs (M ¼ Be, Sc, Ni, Pd, Pt, and Rh) with methane.…”
Section: Introductionsupporting
confidence: 82%
“…[17][18][19][20][21][22][23][24] The experimentally observed reaction efficiency and methanol/ methyl product branching ratio can be rationalized in terms of the calculated barrier heights at the transition states (TSs). [21,23] Li and coworkers [25] have theoretically explored the reaction mechanism of methane with OsO þ . They suggested that the most likely reaction path proceeds via the following:…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] An activation of the C H bond is obviously the very first step in all such processes. However, already the interaction between a metal oxide cation MO + with methane is supposed to undergo a variety of different reaction paths leading to different products.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al have theoretically explored the reaction mechanism of methane with OsO ? [46]. They suggested that the most likely reaction paths is the following: ?…”
Section: )mentioning
confidence: 99%